“It's a Valuable Service but a Hard Place to Be:” Women's Views About Violence Against Women Shelters - Tutty, Leslie M. (Violence against women, 2025)
This mixed-methods secondary analysis examined VAW shelter use by 662 Canadian women abused by partners (50.5% Indigenous, 43.4% White, and 6.1% visible minority). Women who had never resided in shelters (n = 242) had less Severe Combined and Total IPV on the Composite Abuse Scale and fewer PTSD symptoms. More nonresidents worked full time and had higher incomes and no children. The 420 women residents mentioned strengths (70.4%) such as supportive staff and safety, and concerns (29.6%) about unsupportive staff and the shelter rules or facility. Some Indigenous women reported racist attitudes by shelter staff and child apprehensions. Practice implications are presented.